Cross-flow filtration for the recovery of lipids from microalgae aqueous extracts: Membrane selection and performances. (February 2020) - Clavijo Rivera, Erika; Villafaña-López, Liliana; Liu, Shuli; Vinoth Kumar, R.; Viau, Michèle; Bourseau, Patrick; Monteux, Cécile; Frappart, Matthieu; Couallier, Estelle
Graphical abstract: Highlights: Membrane filtration is a promising fractionation process for microalgae biorefining. A model solution was formulated to avoid product variability and to test membranes. A polyacrylonitrile membrane showed the best performances for lipids concentration. The membrane filtration of real microalgae extracts showed similar permeate flux. Proper disruption and filtration operating conditions will allow fractionation. Abstract: The biorefinery of microalgae necessitates innovative choices of soft and energy-efficient processes to guarantee the integrity of fragile molecules and develop eco-friendly production. A wet processing of biomass is proposed, which avoids expensive drying steps. It includes harvesting, cell disruption, and fractionation of the target compounds. Membrane filtration is a promising clean fractionation step. In this paper, the recovery of lipids from starving Parachlorella kessleri aqueous extracts by cross-flow filtration was studied. A model solution was formulated to test four membranes of different materials (PVDF, PES, PAN) and cut-offs (200 kDa – 1.5 μ m). The hydrophilic PAN 500 kDa membrane presented the best performance (flux stability, permeate flux, lipid retention, and cleanability) and was therfore selected for filtrating real aqueous extracts. Similar permeation fluxes were obtained with model and real products: 34–41 L h − 1 m − 2 respectively. The coalescence of lipid droplets was observed with model solutions but not with real products, less concentrated. The lipids from the real products were wholly retained by the PAN membrane, whereas some of the polysaccharides and proteins were able to permeate. An optimization of the coupling between culture, cell disruption, clarification, and filtration would allow a good concentration and purification of the lipids from microalgae.